Aspectos de poética indo-europeia: recursos estilísticos empregados no gênero hínico nas tradições grega e indiana - Moura, Valmir Nascimento de (2019)
Based on the assumption that the hypothetical language known as Indo-European can transmit features as an inheritance to the languages derived from it so that it is possible to reconstruct its grammaticality, I suppose that, based on the theory of Watkins (1995), to rebuild the basic schemes of a poetic language applied to the genre of hymns is equally possible. In order to try to prove this hypothesis, one should carry out a comparative analysis between hymns which were made in Greece and in India – two genuinely Indo-European traditions that have attested antiquity since the second millennium BCE. This study aims at recognizing, in both cultures, stylistic elements employed by the poets that could be inherited from their linguistic ancestor for the production of this literary genre. Firstly, the term Indo-European is concisely defined and the principles, by which linguistic and cultural heredity is possible, are recognized based on the works of scholars such as Benveniste, Meillet, West and Campanile, on the one hand, and of scholars like Dumezil, Berger and Bakthin, on the other hand. Next, the Indo-European institution known as poet and its artistic production in general is discussed, according to the surviving documentation in several branches of this linguistic family, and the genre of hymns is conceptualized, verifying the existence of such analogous literary production in Greece and in India. Finally, by constructing the corpus from the Homeric Hymns, the Orphic Hymns and the Rig-Veda, both complete compositions and excerpts within the Greek and Indian traditions are analyzed, highlighting the most significant elements employed in the constitution and structuring of the hymnal genre. This research points to a strong indication of continuity of a tradition that can be perceived by the similarity and use of poetic resources, but it also points to innovations through the production of their own features and tendencies of choice in the way of use of these resources by each culture.